A mathematical fuzzy logic control systems model using rough set theory for robot applications - Africa, Aaron Don M. (Animo Repository, 2017)
Robotics is an important technology that can aid humans in a variety of ways. These devices can help humans in fields like car production, military service, commercialized agriculture and space exploration. A robot is essentially a mechanical device that can be programmed to follow a specific set of instructions. One problem that is usually encountered in robotics is there are instances when its output is in degrees of truth of either 0 or 1. This is a challenge because robotic representations must not be limited to specific degrees of truth; it must have the ability to be represented in a wide variety of ranges. This research solves that problem by applying Fuzzy Logic Control Systems to robotic representations specifically in the delta-speed motor control area. This provides the Mathematical Model the ability to represent robotic representations of delta-speed motor control to a wide variety of ranges. The output of the Mathematical Model is in the decision rules that show the delta-speed motor control in a wide variety of ranges. Rough Set Theory is then applied to the model in order to turn the rules into nominal form to simplify the rules so that only the necessary parameters are needed to obtain the output. A prototype was created to demonstrate the Mathematical Model of this research with the aid of Lego Mindstorms EV3. The Lejos EV3 Java framework and MATLAB was used to program and demonstrate the Mathematical Model of the robot.